Automation of Semantic Annotations on the Example of Ontea System - Gołuchowski, Jerzy; Knapik, Barbara (Automatyzacja semantycznych adnotacji na przykładzie systemu Ontea, 2010)
One of the most onerous daily activities in organisation is searching and scanning documents. Indexing of documents used in the Document Management Systems is characterized by many limitations. Semantic description of documents, called semantic annotation, allows its users to automate the process of documents' searching. By using automatic or halfautomatic annotation, user cannot only benefit from the already created annotations but develop new ones, which may be re-used in the future. The key objective of the article is to present the concept of annotation as one of the approaches towards semantic description of documents, and automatic creation of semantic annotations. Ontea - one of the most popular tools for creating semantic annotation - is presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 30-41
Keywords: semantic annotation; ontology; semantic web; taxonomy; identifier of object; knowledge base; document indexing